PERAN REGULASI DALAM MEREKONTRUKSI PURI UKIR KAWI CAKRANEGARA TERHADAP UPAYA PENINGKATAN KUALITAS KEPARIWISATAAN DAERAH - ARTA, I PUTU SUGIH (Prodi Hukum Agama Hindu Jurusan Dharma Sastra STAHN Gde Pudja Mataram, 2018)
Regulation is needed by the community to ensure fairness in achieving common goals. Starting from the Act until the Regional Regulation becomes a reference in implementing activities for the common good. Regarding the reconstruction of a place that has a historical value required guarantees for the process goes well certainly requires the principle of justice based on legal footing.Puri Ukir Kawi Cakranegara built by AA Gde Ngurah Karangasem in the past, has been known to exist based on information records Capt.W.Cool in his expedition in Lombok in 1894. Condition, now almost partially destroyed by colonialism invaders need serious attention to be restored.In addition to having the value of local wisdom Puri Ukir Kawi Cakranegara can bring in foreign exchange from the tourism sector. To that end, the local government immediately took steps to reconstruct and revitalize the existence of the castle.